Real‐Time Detection of Protein Trafficking with High‐Throughput Flow Cytometry (HTFC) and Fluorogen‐Activating Protein (FAP) Base Biosensor. Issue 1 (16th February 2018) - Wu, Yang; Tapia, Phillip H.; Jarvik, Jonathan; Waggoner, Alan S.; Sklar, Larry A.
Abstract: We combined fluorogen‐activating protein (FAP) technology with high‐throughput flow cytometry to detect real‐time protein trafficking to and from the plasma membrane in living cells. The hybrid platform allows drug discovery for trafficking receptors, such as G protein–coupled receptors, receptor tyrosine kinases, and ion channels, which were previously not suitable for high‐throughput screening by flow cytometry. The system has been validated using the β2‐adrenergic receptor (β2AR) system and extended to other GPCRs. When a chemical library containing ∼1200 off‐patent drugs was screened against cells expressing FAP‐tagged β2AR, all known β2AR active ligands in the library were successfully identified, together with a few compounds that were later confirmed to regulate receptor internalization in a nontraditional manner. The unexpected discovery of new ligands by this approach indicates the potential of using this protocol for GPCR de‐orphanization. In addition, screens of multiplexed targets promise improved efficiency with minor protocol modification. Curr. Protoc. Cytom . 67:9.43.1‐9.43.11. © 2014 by John Wiley & Sons, Inc.